Passionate organization : igniting the fire of employee commitment - Lucas, James R. (American Management Association New YorkUS, 1999)
Examines the nature of positive passion, the power of passion, and the passionate organization. Explores issues including: the limitations of reason; the role of passion in enabling learning/teaching in organizations; and clues to discerning the presence of passion in organizations. Looks at various aspects of building the passionate organization including: hiring and preparing passionate people; building passion for stakeholders e.g. customers, shareholders etc.; and, dealing with waning, negative and missing passion. Examines problems of traditional management practice and proposes the self-management, leadership-at-all-levels paradigm.